Pemecahan Masalah Bagi Dewasa Madya Berlandaskan Pendidikan Agama Kristen - Sihombing, Cindy Sriwahyuni; Simbolon, Yuli Arta; Tampubolon, Friska Elisabet; Damayanti Nababan (Publisher STPKat, 2024)
Adulthood is experiencing many problems that must be faced, especially in middle adulthood. Middle adulthood can be said to start at 35-60 years old. The median age is filled with various responsibilities and roles that consume time and energy. This period is also a period that spans the problems of daily life faced. This period was eventually marked by physical and mental changes, especially in spirituality. The method used in this paper is qualitative, using a literature approach. A literature study is carried out by examining various sources regarding the topics discussed. Researchers use various study sources such as textbooks, scientific journals and scientific internet sources.